The PAF1 complex cell autonomously promotes oogenesis in Caenorhabditis elegans. (27th April 2022) - Kubota, Yukihiro; Ota, Natsumi; Takatsuka, Hisashi; Unno, Takuma; Onami, Shuichi; Sugimoto, Asako; Ito, Masahiro
Abstract: The RNA polymerase II‐associated factor 1 complex (PAF1C) is a protein complex that consists of LEO1, RTF1, PAF1, CDC73, and CTR9, and has been shown to be involved in RNA polymerase II‐mediated transcriptional and chromatin regulation. Although it has been shown to regulate a variety of biological processes, the precise role of the PAF1C during germ line development has not been clarified. In this study, we found that reduction in the function of the PAF1C components, LEO‐1, RTFO‐1, PAFO‐1, CDC‐73, and CTR‐9, in Caenorhabditis elegans affects oogenesis. Defects in oogenesis were also confirmed using an oocyte maturation marker, OMA‐1::GFP. While four to five OMA‐1::GFP‐positive oocytes were observed in wild‐type animals, their numbers were significantly decreased in pafo‐1 mutant and leo‐1(RNAi), pafo‐1(RNAi), and cdc‐73(RNAi) animals. Expression of a functional PAFO‐1::mCherry transgene in the germline significantly rescued the oogenesis‐defective phenotype of the pafo‐1 mutants, suggesting that expression of the PAF1C in germ cells is required for oogenesis. Notably, overexpression of OMA‐1::GFP partially rescued the oogenesis defect in the pafo‐1 mutants. Based on our findings, we propose that the PAF1C promotes oogenesis in a cell‐autonomous manner by positively regulating the expression of genes involved in oocyte maturation.